2020
DOI: 10.1089/pancan.2019.0014
|View full text |Cite
|
Sign up to set email alerts
|

Is There a Trojan Horse to Aggressive Pancreatic Cancer Biology? A Review of the Trypsin-PAR2 Axis to Proliferation, Early Invasion, and Metastasis

Abstract: Purpose: Pancreatic cancer is one of the most lethal of solid tumors and is associated with aggressive cancer biology. The purpose is to review the role of trypsin and effect on molecular and cellular processes potentially explaining the aggressive biology in pancreatic cancer. Methods: A narrative literature review of studies investigating trypsin and its effect on protease systems in cancer, with special reference to pancreatic cancer biology. Results: Proteases, such as trypsin, provides a significant advan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 67 publications
(82 reference statements)
0
6
0
Order By: Relevance
“…LYVE1 is reported to be elevated in urine of patients with PDAC, enough to be one of three biomarkers to stratify cancer risk [ 48 ], with no data on cachexia. PRSS1 aka trypsin/trypsinogen mutations increase risk of chronic pancreatitis and pancreatic cancer [ 49 ] and its pathological activation promotes neoplasia [ 50 ]. The ratio of PRSS1 and its inhibitor SERPINA1 or alpha-1-antitrypsin is elevated in patients with PDAC [ 51 ], and SERPINA1 deficiency is associated with pancreatitis and cachexia phenotypes [ 52 ].…”
Section: Discussionmentioning
confidence: 99%
“…LYVE1 is reported to be elevated in urine of patients with PDAC, enough to be one of three biomarkers to stratify cancer risk [ 48 ], with no data on cachexia. PRSS1 aka trypsin/trypsinogen mutations increase risk of chronic pancreatitis and pancreatic cancer [ 49 ] and its pathological activation promotes neoplasia [ 50 ]. The ratio of PRSS1 and its inhibitor SERPINA1 or alpha-1-antitrypsin is elevated in patients with PDAC [ 51 ], and SERPINA1 deficiency is associated with pancreatitis and cachexia phenotypes [ 52 ].…”
Section: Discussionmentioning
confidence: 99%
“…Tumor-associated trypsin has been recognized as a significant factor in cancer progression and metastatic processes. 28 As the precursor of trypsin, PRSS2 seems to be strongly correlated with cancers in 4 trypsin isoforms. 29 Several studies revealed high trypsinogen expression in different CRC cell lines.…”
Section: Resultsmentioning
confidence: 98%
“…Effective FDA approved, early detection assays for PDAC detection are nonexistent, but are critically needed to transform survival from this deadly disease. The only FDA approved clinical biomarker for PDAC is carbohydrate antigen 19-9 (CA19-9), which is used predominantly for measure of disease burden across treatment and not as an early detection biomarker, due to its low positive predictive value (PPV) in this setting (1)(2)(3)(4)(5). Currently, our ability to screen the general population as well as monitor patients at high-risk for PDAC is limited by many factors including access, cost, and assay accuracy.…”
Section: Introductionmentioning
confidence: 99%